ANALISIS PENGARUH JUMLAH INDUSTRI BESAR DAN UPAH MINIMUM TERHADAP PERTUMBUHAN EKONOMI DI KOTA SURABAYA - Julianto, Foengsitanjoyo Trisantoso; ., Suparno (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
Summary The study entitled "Analysis of Effect of Number of Large and Minimum Wages Against Economic Growth in Surabaya" aims to determine the effect of the number of large industrial and minimum wages to economic growth in the city of Surabaya and also to determine which variable most dominant influence in economic growth in the city Surabaya. The types and sources of data used quantitative approach with secondary data time series observations in the period 2009-2013. The research variables consist of the dependent variable is economic growth (Y). The independent variable is the number of large industries (X1), the minimum wage (X2). Tools data analysis using multiple linear regression, t-test, f and the coefficient of determination. Based on the results of multiple linear regression analysis obtained the following results: Y = 8.898 + 0,511X1 0,310X2 + e +. From the results obtained by multiple linear regression analysis of multiple determination coefficient (R2) of 0.513, or 51.3%, and also the value of Fhitung 24.375> Ftable 19,000 with significance 0.039 <0.05. While tcount (X1) of 6.074> ttabel 4.3027 with a significance of 0.026 <0.05, thitung (X2) of 4.519> 4.3027 ttabel with significance 0.046 <0.05. The conclusion of this study showed that the number of large industrial and minimum wages affect the economic growth in the city of Surabaya. While most dominant variable in economic growth in the city of Surabaya is a variable number of big industry because it has a partial determination coefficient (r2) of 0.5358.Keywords: Number of Large, Minimum Wage, Economic Growth